Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Untuk Meningkatkan Hasil Belajar Siswa - Ratih Purwanti; Zainuddin Zainuddin; Suyidno Suyidno (Berkala Ilmiah Pendidikan Fisika, 2014)
Nature of education is to optimize the learning outcomes of cognitive, affective, and psychomotor students, but in fact, the result of students of class X-1 SMAN 1 Anjir Pasar is still low. Conducted research described the effectiveness of the cooperative learning model TTW in improving student learning outcomes. The specific aims of this research describe feasibility RPP, learning outcomes, social skills, and student response. The research using classroom action research model of Hopkins which consists of 3 cycles include planning, action/observation, and reflection. The research subjects consisted of 28 students. The data obtained through the tests, observations, questionnaires, and documentation. The data were analyzed by descriptive qualitative and quantitative. The findings of research showed: (1) feasibility RPP in cycle I, II, III respectively 79,40%; 91,90%; 95,83%, (2) an increase in exhaustiveness of students learning outcomes in classical the first cycle of 72,0% (not completed), the second cycle of 88,5% (complete), and the third cycle was 92,0% (complete), (3) social skills of students in the first cycle is generally pretty good, the second cycle increased to well, and a very good third cycle, and (4) students positive response to cooperative learning model TTW generally good. Conclusion of research is the effectiveness of application of cooperative learning model TTW in improving student learning outcomes in class X-1 SMAN 1 Anjir Pasar on the subject of heat transfer categorized effectively.